Hope across cultures Lessons from the International Hope Barometer - Krafft, Andreas M.; Guse, Tharina; Slezackova, Alena (Cross-Cultural Advancements in Positive Psychology, 2023)
This open access book presents an integrative and transdisciplinary conceptualization of hope and brings together cross-cultural studies based on quantitative data from around the globe. It incorporates state-of-the-art theories of hope from psychology, philosophy and theology and presents a novel approach to the study of hope in different life situations. The volume analyses empirical data from the Hope Barometer international research network, collected from more than 40,000 participants between 2017 and 2021. The authors use this broad database to investigate the nature and value of hope for well-being and flourishing at individual and societal levels, in various regions, and different cultural, religious and social backgrounds. The chapters study the cultural characteristics of different facets and elements of hope and furthermore explore its common qualities to elucidate the universal nature of hope across cultures. Comprehensive, transdisciplinary and cross-cultural in scope, this volume is of interest to a global readership across the social and behavioural sciences.